Facile synthesis of elemental sulfur-mediated fluorine-containing covalent triazine frameworks and their performance in lithium–sulfur batteries. (22nd March 2023) - Wang, Shuhao; Song, Yue; Wang, Zhao; Xie, Wei; Zhang, Shuran; Yao, Chan; Zhao, Yanning; Xu, Yanhong
Abstract : The structure diagram of SFN-CTFs and the cycle diagram of SFN-CTF(1 : 2)-1 are presented. Abstract : Covalent triazine frameworks (CTFs) are considered as ideal potential cathode composites for anchoring lithium sulfide compounds. In this paper, five fluorine-containing CTF materials (FN-CTFs) were successfully prepared by modulating the molar ratio of the feeding monomers TFTN and DCB. During the experiment, the optimal content of sulfur was determined to be 71.92% (mass fraction) by adjusting the sulfur content. The initial discharge capacity of the composite electrode at a rate of 0.5C is 959.5 mA h g −1, and after 200 charge–discharge cycles, the residual rate of discharge capacity is 71.32%, and the discharge capacity is 684.3 mA h g −1 . Sulfur utilization, cycling stability and multiplier performance of the SFN-CTF composite cathodes are all superior to those of sulfur cathodes.